EKSISTENSI CHEN YAN XIANG: PEDAGANG, DIPLOMAT, DAN DIASPORA: Merchant, Diplomat, and Diaspora - Santoso, Christopher Jason (Balai Pelestarian Kebudayaan Wilayah X, 2023)
Chen Yan Xiang might be the first-and-only person from Majapahit Kingdom which came throughout Korea Peninsula and noted by Veritable Records of Joseon Dynasty at the end of 14th until the beginning of 15th century. Foreign records have verified his legacy as diplomat, though countless aspects challenged him before gone to Joseon Kingdom. But the information for Chen Yan Xiang is still little to know about, especially about his identity, legacy, and role during history. Researcher’s objectives are to explore more his legacy from Majapahit to East Asia, especially Korea Peninsula and Japan from his role towards as being a merchant, a diplomat, and a diaspora. Researcher’s method is qualitative research with comparative style of verification to old documents. Chen Yan Xiang was believed to be not only a diplomat, but also a merchant for goods from Java, and the diaspora – making cultural and linguistic connections between two old countries.